Politeness in making complaints amongst college students / Lim Sheau Wei - Lim , Sheau Wei (2013)
This study focuses on the politeness in making complaints among college students. Focusing on 15 male and 15 female Chinese Malaysia respondents who are studying in a private college in Malacca, data was extracted via two approaches. First, a set of tasks were provided to the participants. They were asked to respond to those tasks accordingly. All the activities took place within the classroom setting and all their responses were tape-recorded. Data were transcribed orthographically and the responses were analysed according to Olshtain and Weinbach’s (1987) framework of the Notion of Severity of the Complaint and Lakoff’s (1975) framework of Politeness Strategies – Lakoff’s Language and Women’s Place. The results of this study suggest that the closer the relationship between the speaker and intended hearer, the more direct the linguistic forms of complaints used, the higher the power of one over another (between the speaker and intended hearer), the more indirect the linguistic forms of complaints used. This study also found that female speakers were more sensitive in such situation and therefore they used more politeness strategies than the male speakers. As a conclusion, it is apparent that power and gender are factors which could affect one’s degree of politeness when behaving in a society, in particular when making complaints.